The sum of all (positive) solutions of the equation
lo g 1 6 x + lo g x 1 6 = lo g 5 1 2 x + lo g x 5 1 2
can be written as b a , where a and b are coprime positive integers. What are the last three digits of a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
thanks
How did you get 4097?????
Let y = lo g 2 x . Then 4 y = 4 lo g 2 x = lo g 2 1 6 lo g 2 x = lo g 1 6 x and 9 y = 9 lo g 2 x = lo g 2 5 1 2 lo g 2 x = lo g 5 1 2 x . In addition, lo g x 1 6 = lo g 1 6 x 1 = y 4 and lo g x 5 1 2 = lo g 5 1 2 x 1 = y 9 . Therefore, the given equation becomes 4 y + y 4 = 9 y + y 9 . Combining fractions on both sides gives 4 y y 2 + 1 6 = 9 y y 2 + 8 1 , and cross-multiplying, we have 9 y ( y 2 + 1 6 ) = 4 y ( y 2 + 8 1 ) . If y = 0 , then x = 2 0 = 1 , which is not a valid solution since lo g x 1 6 is not defined if x = 1 . Thus, we can divide both sides by y to obtain the following: 9 ( y 2 + 1 6 ) 9 y 2 + 1 4 4 5 y 2 y 2 y = 4 ( y 2 + 8 1 ) = 4 y 2 + 3 2 4 = 1 8 0 = 3 6 = ± 6 . Therefore, either lo g 2 x = 6 , so x = 2 6 = 6 4 , or lo g 2 x = − 6 , so x = 2 − 6 = 6 4 1 . The sum of these two solutions is 6 4 + 6 4 1 = 6 4 4 0 9 7 , and the last three digits of 4 0 9 7 + 6 4 = 4 1 6 1 are 1 6 1 .
Although it's pretty much the same solution as everyone else's, this one's really neatly written. Good job, you have my vote!
Using the identity that -
l o g b a = l o g m b l o g m a ,
Taking the bases as 2 [As we see that 1 6 and 5 1 2 are powers of 2 ] ,
and thus our simplified equation will be -
l o g 2 1 6 l o g 2 x + l o g 2 x l o g 2 1 6 = l o g 2 5 1 2 l o g 2 x + l o g 2 x l o g 2 5 1 2
⇒ 4 l o g 2 x + l o g 2 x 4 = 9 l o g 2 x + l o g 2 x 9
⇒ 4 l o g 2 x − 9 l o g 2 x = l o g 2 x 9 − l o g 2 x 4
⇒ ( l o g 2 x ) ( 4 1 − 9 1 ) = ( l o g 2 x 1 ) ( 9 − 4 )
⇒ ( l o g 2 x ) ( 3 6 5 ) = ( l o g 2 x 5 )
⇒ ( l o g 2 x ) ( 3 6 1 ) = ( l o g 2 x 1 )
Now by transposing the constant terms to one side ,
⇒ ( l o g 2 x ) 2 = 3 6
⇒ l o g 2 x = ± 6
⇒ x = 2 ± 6
Thus , we get x = 2 6 = 6 4 and x = 2 − 6 = 6 4 1
Thus the sum of values of x
= 6 4 + 6 4 1 = 6 4 4 0 9 7
Thus a + b = 4 0 9 7 + 6 4 = 4 1 6 1
And hence , last three digits are 1 6 1
Cheers!
We let l o g 1 6 x = k . Then l o g x 1 6 = k 1 . Also, since l o g 5 1 2 1 6 = l o g 2 9 2 4 = 9 4 , l o g 5 1 2 x = ( l o g 1 6 x ) ( l o g 5 1 2 1 6 ) = ( k ) ( 9 4 ) = ( 9 4 k ) . Hence l o g x 5 1 2 = 4 k 9 .
Now we solve the equation. In terms of k , the equation becomes k + k 1 = 9 4 k + 4 k 9 . Thus k − 9 4 k = 4 k 9 − k 1 . Hence 9 5 k = 4 k 2 5 k . Thus 4 k 2 = 9 , and k 2 = 4 9 . k = ± 2 3 .
If k = 2 3 , then x = 1 6 2 3 = 6 4 . If k = − 2 3 , x = 1 6 2 3 1 = 6 4 1 .
Thus the sum of all positive solutions is 6 4 1 + 6 4 = 6 4 6 4 2 + 1 = 6 4 4 0 9 7 .
Hence a = 4 0 9 7 and b = 6 4 . a + b = 4 1 6 1 , so the last 3 digits of a + b is 1 6 1 .
lo g 1 6 x + lo g x 1 6 lo g 2 1 6 lo g 2 x + lo g 2 x lo g 2 1 6 4 lo g 2 x + lo g 2 x 4 ( 4 1 − 9 1 ) lo g 2 x ( 3 6 5 ) lo g 2 x ( lo g 2 x ) 2 ⇒ lo g 2 x x 6 4 + 6 4 1 = lo g 5 1 2 x + lo g x 5 1 2 = lo g 2 5 1 2 lo g 2 x + lo g 2 x lo g 2 5 1 2 = 9 lo g 2 x + lo g 2 x 9 = lo g 2 x 9 − 4 = lo g 2 x 5 = 3 6 = ± 6 = { 2 6 = 6 4 2 − 6 = 6 4 1 = 6 4 4 0 9 7
⇒ a + b = 4 0 9 7 + 6 4 = 4 1 6 1
We may rewrite the equation this way:
lo g 1 6 x − lo g 5 1 2 x = lo g x 5 1 2 − lo g x 1 6
Note that the RHS is equal to lo g x 1 6 5 1 2 = lo g x 3 2
We can change the base of every expression on the LHS to 1 6
We have the LHS equal to lo g 1 6 x − lo g 1 6 5 1 2 lo g 1 6 x
Note that lo g 1 6 5 1 2 = 4 9 . We have the equation:
lo g 1 6 x − 9 4 lo g 1 6 x = lo g x 3 2 or 9 5 lo g 1 6 x = lo g x 3 2
We may change the base of the RHS to 1 6 and thus:
lo g x 3 2 = lo g 1 6 x lo g 1 6 3 2 . We now have the equation equal to:
9 5 ( lo g 1 6 x ) 2 = lo g 1 6 3 2 , but lo g 1 6 3 2 = 4 5
Therefore: ( lo g 1 6 x ) 2 = 4 9 ⇒ lo g 1 6 x = ± 2 3
x = 4 ± 3 so the sum of all solutions is 6 4 + 6 4 1 = 6 4 4 0 9 7
a + b = 4 1 6 1 , 1 6 1 is the answer.
l o g 1 6 x + l o g x 1 6 = l o g 5 1 2 x + l o g x 5 1 2
l o g 2 2 4 l o g 2 x + l o g 2 x l o g 2 2 4 = l o g 2 2 9 l o g 2 x + l o g 2 x l o g 2 2 9
4 l o g 2 x + l o g 2 x 4 = 9 l o g 2 x + l o g 2 x 9
4 l o g 2 x − 9 l o g 2 x = l o g 2 x 9 − l o g 2 x 4
3 6 5 × l o g 2 x = l o g 2 x 5
( l o g 2 x ) 2 = 3 6
l o g 2 x = 6 or l o g 2 x = − 6
x = 2 6 or x = 2 − 6
6 4 + 6 4 1 = 6 4 4 0 9 6 + 1 = 6 4 4 0 9 7
So a = 4 0 9 7 and b = 6 4
a + b = 4 1 6 1
And the last three digits are 1 6 1
lo g 1 6 x + lo g x 1 6 = lo g 5 1 2 x + lo g x 5 1 2 . Using the change-of-base rule, we have lo g 2 1 6 lo g 2 x + lo g 2 x lo g 2 1 6 = lo g 2 5 1 2 lo g 2 x + lo g 2 x lo g 2 5 1 2 , so 4 lo g 2 x + lo g 2 x 4 = 9 lo g 2 x + lo g 2 x 9 . Simplifying, we get 3 6 5 lo g 2 x = lo g 2 x 5 ⟹ ( lo g 2 x ) 2 = 3 6 .
⟹ lo g 2 x = ± 6 ⟹ x = 2 ± 6 .
⟹ x ∈ { 6 4 , 6 4 1 } .
⟹ ∑ x = 6 4 + 6 4 1 = 6 4 4 0 9 7 , so our answer is ( 4 0 9 7 + 6 4 ) m o d 1 0 0 0 ≡ 4 1 6 1 m o d 1 0 0 = 1 6 1 .
Let lo g 2 x = t then we can write the equation as: t / 4 + 4 / t = t / 9 + 9 / t t 2 = 3 6 So we have t = 6 or t = − 6 which means x = 6 4 or x = 1 / 6 4
There are certain laws of logarithms required for this question. I shall list them below.
lo g a b n = n lo g a b
lo g a a = 1
lo g a b = lo g c a lo g c b where c can be any number whatsoever. In this case we will chose c = 2 for convenience as all the numbers provided are powers of 2
Now we are set
lo g 1 6 x + lo g x 1 6 = lo g 5 1 2 x + lo g x 5 1 2
lo g 2 1 6 lo g 2 x + lo g 2 x lo g 2 1 6 = lo g 2 5 1 2 lo g 2 x + lo g 2 x lo g 2 5 1 2
note that lo g 2 1 6 = lo g 2 2 4 = 4 lo g 2 2 = 4 Similarly, lo g 2 5 1 2 = 9
4 lo g 2 x + lo g 2 x 4 = 9 lo g 2 x + lo g 2 x 9
Multiplying throughout by 3 6 lo g 2 x gives us
9 ( lo g 2 x ) 2 + 1 4 4 = 4 ( lo g 2 x ) 2 + 3 2 4
let y = lo g 2 x
9 y 2 + 1 4 4 = 4 y 2 + 3 2 4
5 y 2 = 1 8 0
y = ± 3 6 = ± 6
lo g 2 x = ± 6
lo g 2 x = 6 or lo g 2 x = − 6
x = 2 6 = 6 4 or x = 2 − 6 = 6 4 1
the sum of all the possible values of x gives us 6 4 + 6 4 1 = 6 4 4 0 9 7
4 0 9 7 + 6 4 = 4 1 6 1 ⇒ the last 3 digits are 1 6 1
lo g 1 6 x + lo g x 1 6 = lo g 5 1 2 x + lo g x 5 1 2
lo g 1 6 lo g x + lo g x lo g 1 6 = lo g 5 1 2 lo g x + lo g x lo g 5 1 2
lo g 2 4 lo g x + lo g x lo g 2 4 = lo g 2 9 lo g x + lo g x lo g 2 9
4 lo g 2 lo g x + lo g x 4 lo g 2 = 9 lo g 2 lo g x + lo g x 9 lo g 2
4 lo g 2 lo g x − 9 lo g 2 lo g x = lo g x 5 lo g 2
3 6 lo g 2 9 lo g x − 3 6 lo g 2 4 lo g x = lo g x 5 lo g 2
3 6 lo g 2 5 lo g x = lo g x 5 lo g 2
3 6 lo g 2 lo g x = lo g x lo g 2
( lo g x ) 2 = 3 6 ( lo g 2 ) 2
lo g x = ± 6 lo g 2
lo g x = lo g 2 − 6 or lo g x = lo g 2 6
lo g x = lo g 6 4 1 or lo g x = lo g 6 4
x = 6 4 1 or x = 6 4
The sum of solutions is 6 4 1 + 6 4 = 6 4 4 0 9 7 . Let a = 4 0 9 7 and b = 6 4 so that a + b = 4 1 6 1 ≡ 1 6 1 mod 1 0 0 0 .
convert everything to lo g 2 to get: lo g 2 1 6 lo g 2 x + lo g 2 x lo g 2 1 6 = lo g 2 5 1 2 lo g 2 x + lo g 2 x lo g 2 5 1 2 4 lo g 2 x + lo g 2 x 4 = 9 lo g 2 x + lo g 2 x 9 Then let y = lo g 2 x which means x = 2 y to get: 4 y + y 4 = 9 y + y 9 9 y 2 + 4 × 3 6 = 4 y 2 + 9 × 3 6 5 y 2 = 5 × 3 6 y 2 = 3 6 y = ± 6 Therefore, x = 2 6 or x = 2 − 6 which means the sum of these solutions is 2 6 + 2 − 6 = 6 4 4 0 9 7 = b a .
Therefore, a + b = 4 0 9 7 + 6 4 = 4 1 6 1 and the last 3 digit are 161.
Note that 16 = 2^4 and 512 = 2^9. For convenience let X denote log x to the base 2. Given equation rewritten in terms of X becomes X/4 + 4/X = X/9 + 9/X. By inspection x = 1 (X=0) cannot be a solution. On multiplying every term by 36 X, we get 9X^2 + 144 = 4X^2 + 324, 5X^2 = 180, X^2 = 36, X = 6 or - 6, x = 64 or 1/64 Sum of the solutions is 4097/64 and 4097+ 64 being 4161. Hence answer is 161.
To begin with, note that for any real values of p and q , lo g q p = lo g m q lo g m p where m is also any real number, which in this solution will be 1 0 .
Therefore
lo g 1 6 x + lo g x 1 6 = lo g 5 1 2 x + lo g x 5 1 2 ⇒
⇒ l g 1 6 l g x + l g x l g 1 6 = l g 5 1 2 l g x + l g x l g 5 1 2 ⇒ l g 1 6 l g x l g 2 x + l g 2 1 6 = l g 5 1 2 l g x l g 2 x + l g 2 5 1 2
Now, using the fact that lo g m n = n lo g m , 1 6 = 2 4 and 5 1 2 = 2 9 , we may conclude
l g 1 6 l g x l g 2 x + l g 2 1 6 = l g 5 1 2 l g x l g 2 x + l g 2 5 1 2 ⇒ l g 2 4 l g x l g 2 x + l g 2 2 4 = l g 2 9 l g x l g 2 x + l g 2 2 9 ⇒ ⇒ 4 l g 2 l g x l g 2 x + 1 6 l g 2 2 = 9 l g 2 l g x l g 2 x + 8 1 l g 2 2 ⇒ l g 2 x + 8 1 l g 2 2 l g 2 x + 1 6 l g 2 2 = 9 4 ⇒
⇒ 9 l g 2 x + 1 4 4 l g 2 2 = 4 l g 2 x + 3 2 4 l g 2 2 ⇒ 5 l g 2 x = 1 8 0 l g 2 2 ⇒
⇒ l g 2 x = 3 6 l g 2 2 ⇒ l g 2 x = l g 2 2 6 ⇒
⇒ l g 2 x − l g 2 2 6 = 0 ⇒ ( l g x − l g 2 6 ) ( l g x + l g 2 6 ) = 0 .
From this, we may derive 2 separate cases:
Case I
l g x − l g 2 6 = 0 ⇒ l g x = l g 2 6 ⇒ x 1 = 2 6
Case II
l g x + l g 2 6 = 0 ⇒ l g x = − l g 2 6 ⇒ l g x = l g 2 − 6 ⇒ x 2 = 2 − 6
Thus, the sum of all the positive solutions equals
x 1 + x 2 = 2 6 + 2 6 1 = 2 6 2 1 2 + 1 = 6 4 4 0 9 7 .
Consequently, b a = 6 4 4 0 9 7 ⇒ a + b = 4 1 6 1 , meaning the answer is 1 6 1 .
Let log2x=m. Then log16x= m/4 And logx16 is its reciprocal, i.e. 4/m. Similarly, log512x=m/9 and logx512=9/m. So the equation can be rewritten as m/4 + 4/m=m/9+9/m. 5m/36=5/m. m^2=36. m=+6, -6. 2^6=64=x. And 2^ (1/6) = 1/64=x. Adding both together, we obtain the sum of all possible values of x as 64+1/64, or 4097/64. Thus a=4097 and b=64. Therefore a + b = 4161. Last 3 digits of (a + b) are 161.
Problem Loading...
Note Loading...
Set Loading...
We write lo g x 1 6 as 4 lo g x 2 , and lo g 1 6 x as lo g x 1 6 1 = 4 lo g x 2 1 . Similarly, lo g x 5 1 2 = 9 lo g x 2 , and lo g 5 1 2 x = 9 lo g x 2 1 . Hence, 4 lo g x 2 + 4 lo g x 2 1 ( 4 1 − 9 1 ) ( lo g x 2 1 ) 3 6 1 ± 6 1 = = = = 9 lo g x 2 + 9 lo g x 2 1 5 lo g x 2 ( lo g x 2 ) 2 lo g x 2 . Hence, x = 6 4 or x = 6 4 1 , and the sum of these is 6 4 4 0 9 7 . We obtain 4 0 9 7 + 6 4 = 4 1 6 1 , and the last three digits are 1 6 1 .